Genetic and chemical diversity of native populations of Ocimum selloi Benth - Facanali, Roselaine [UNESP]; Colombo, Carlos A.; Teixeira, Joao P. F.; Ming, Lin C. [UNESP]; Zucchi, Maria I.; Marques, Marcia O. M. (Elsevier B.V., 2015)
The present work aimed to characterize the chemical composition of essential oils and genetic diversity of three native populations of Ocimum selloi collected in Brazil southern and southeastern. Thus, with the proposals to subsidize genetic improvement programs for the species preservation and commercial application of the essential oil. A total of 60 samples from Iporanga and Piquete counties (State of Sao Paulo) and Adrianopolis county (State of Parana) were analyzed by RAPD - genetic polymorphism - and GC-MS - chemical composition of essential oils. The data showed that the variation of the chemical composition of the essential oils of the samples was influenced by geographical region and genetic factors. The Piquete population was more homogeneous with respect to factors evaluated, and presented germacrene D, elemicin, trans-alpha-bergamotene, and bicyclogermacrene as the major components. Populations of Adrianopolis and Iporanga showed strong variability probably due to the gene flow between these populations, because they are geographically close. Most samples of these two regions had as major substances elemicin, beta-selinene, and beta-4-copaen-alpha-ol. The results showed a great genetic and chemical divergence among and inside the populations between, being the diversity inside the populations bigger than among populations. The oils presented potential for commercial use in the manufacture of veterinary, pharmaceutical, and agricultural products. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Paregoric elixir; RAPD; Genetic diversity; Essential oil